Terrain, Land Use and Waste Drilling Fluid Disposal Problems, Arctic Canada - French, Hugh M. (ARCTIC, 1980)
A survey of over 60 abandoned wellsites in the Mackenzie Delta, the Arctic Islands and the interior Yukon Territory indicated that approximately 25% of the sites experienced terrain problems related either directly or indirectly to sumps and/or the containment of waste drilling fluids. These problems are classified as follows: (A) non-containment during drilling, (B) melt-out problems during summer operations, and (C) restoration problems. Fewest problems are associated with one-season winter drilling operations. Two-season winter drilling, in which the sump is left open during the summer, and one-season summer drilling operations present more problems.